Mg-ion conducting electrolytes based on chitosan biopolymer host for the rechargeable Mg batteries. (2022) - Adlin Helen, P.; Perumal, P.; Sivaraj, P.; Infanta Diana, M.; Christopher Selvin, P.
Abstract: Chitosan (CS) biopolymer electrolytes incorporated with MgCl2 prepared by simple solution casting technique were investigated and reported. The structural properties of the electrolytes were analyzed by X-Ray Diffraction technique. The interaction between salt and polymer host was determined from FTIR studies. TG analysis was carried out to study the thermal stability. Using AC impedance spectroscopy, ionic conductivity was calculated and higher values of conductivity was found to be ∼1.255 × 10 −4 Scm −1 for the electrolyte with 70 wt% of MgCl2 and the same can be suggested for the application of electrochemical devices.